Emergency remote teaching: challenges and opportunities in foreign languages applied to tourism - Cardoso, Paula (2021)
The current paper intends to identify and analyse the challenges that both students and faculty have experienced during the process of moving online and that need to be turned into opportunities, in order to avoid replicating traditional teaching in an online environment. They are numerous and at several different levels. On one hand, students have experienced challenges such as time management, support and follow-up, communication and motivation, among others. On their turn, faculty have had difficulties in adapting the resources and, consequently, in mastering the necessary tools and skills, as well as the most suitable pedagogical strategies. On the other hand, assessment may represent a challenge on its own, both for students and faculty. By looking at the example of a Curricular unit of Foreign Languages applied to Tourism, the paper also aims to point out that the main opportunity lies in planning online teaching and learning activities as a conversational process between three axes: learning goals, learning strategies and assessment.